Dong Thap university journal of science : Social Sciences and Humanities Issue Volume 14 - Number 3 (Dong Thap Dong Thap university, 2025)
This issue includes the following articles: Applying TDI index in assessing teacher development at public universities in the Mekong Delta ; TESOL graduates' views on the impacts and ethical aspects of ChatGPT in academic writing ; Impacts of social media on English language acquisition among English-Majored students ; Teaching exponential function properties: Practical and experiential activities on smartphone...
Keywords: Tạp chí